Effect of hot water on the mechanical performance of unidirectional carbon fiber-reinforced nylon 6 composites. (10th November 2020) - Ma, Yan; Jin, Shanshan; Yokozeki, Tomohiro; Ueda, Masahito; Yang, Yuqiu; Elbadry, Elsayed A.; Hamada, Hiroyuki; Sugahara, Toshi
Abstract: One of the major concerns of carbon fiber-reinforced nylon 6 composites (CF/Nylon 6) is its sensitivity to environmental degradation, especially hygrothermal aging. In this study, neat nylon 6 plates and unidirectional CF/Nylon 6 laminates with different fiber orientations manufactured by hot compression method were subjected to water absorption tests by immersing them in 80 °C and 98 °C hot water for various time durations. The corresponding flexural mechanical properties, including the flexural modulus and flexural strength, of the as-prepared samples before and after water absorption were evaluated by using three-point bending tests. The effects of immersion time, fiber orientation, and water temperature on the flexural properties are discussed. Flexural cyclic tests were conducted to evaluate the stiffness degradation of neat nylon 6 and unidirectional CF/Nylon 6 laminates. Optical observation and scanning electron microscopy were used to observe the fracture behavior of unidirectional CF/Nylon 6 laminates before and after water absorption. Results indicated that the flexural modulus and strength of unidirectional CF/Nylon 6 laminates in different fiber orientations decreased by ≈ 8%–60% and ≈40%–60% after hot water immersion, which was mainly caused by the weakened matrix (the cleavage reaction of the main chain and plasticization of the matrix) and weakened interfacial properties (attack on the interface by hot water). The fracture behavior of 0° CF/Nylon 6 laminates after water immersion tended to be more ductile than those without hot water immersion. Graphical abstract: Image 1